Considerations on the species complex of the Cortelezzii series (Diptera: Psychodidae) and description of Evandromyia chacuensis sp. nov., a new phlebotomine species of the Chaco Region, Argentina - Szelag, Enrique Alejandro (2018)
A new species of phlebotomine sand fy is described and illustrated based on male and female specimens collected in rural and semi-urban areas of the Chaco Province, Argentina. A separation of the Cortelezzii series in two species complexes is proposed, as is a species key for its identification. The morphological characters of the new species permit its inclusion in the Cortelezzii series of genus Evandromyia, subgenus Barrettomyia (Diptera: Psychodidae). The species is named Evandromyia chacuensis sp. nov. Szelag, Rosa, Galati, Andrade Fhilo & Salomón (Diptera: Psychodidae).